Chloride-induced corrosion of a galvanized steel-embedded calcium sulfoaluminate stucco system. (December 2021) - Sereewatthanawut, Issara; Pansuk, Withit; Pheinsusom, Phoonsak; Prasittisopin, Lapyote
Abstract: The study of steel corrosion in steel-reinforced cementitious system has attracted much attention because this system is used in key buildings and infrastructure, and, thus, its deterioration represents a significant hazard. In many constructions, the top cement surface is coated with a stucco system. In this study, we present experimental results on the corrosion behavior of a rapid-set stucco composite consisting of calcium sulfoaluminate cement (CSA). The rapid-set stucco is a new product on the market and was designed to improve the practicality of stucco use, which typically requires three coatings. Our test results indicate that the structure is not influenced by the fine aggregate (FA) content but is affected by the water-to-cement (w/c) ratio. The w/c ratio affects the apparent diffusivity ( D a ) of chloride ions penetrating the structure. The pH results indicate that the passivation layer is not formed, leaving a doubt that the CSA stucco should be in use, especially for non-galvanized steel reinforced system. To reduce the negative effect of absence of passivation layer, uniform mixing and casting mixture having good workability is needed which can prolong its serviceability up to 3 times. The use of galvanized steel is also essential which can be increase its service life for at least 5 to 10 times. This is because zinc layer from galvanization process also greatly decreases the corrosion rate by 475% less than that of steel layer itself. Highlights: The pH of the CSA pore fluid is not greater than 13, suggesting that a passivation layer of the embedded steel is not formed . The Zn layer from galvanization process also greatly decreases the corrosion rate (475% better than that of Fe itself). Good mixture preparation prolongs service life by 3 times and using galvanized steel extends its service life up to 10 times.